Benefits and Risks of Lowering Sodium Through Potassium-enriched Salt Substitution for Patients with Chronic Kidney Disease in China: A Modelling Study (OR25-05-19). (13th June 2019) - Marklund, Matti; Singh, Gitanjali; Greer, Raquel; Cudhea, Frederick; Matsushita, Kunihiro; Micha, Renata; Brady, Tammy; Zhao, Di; Huang, Liping; Tian, Maoyi; Cobb, Laura; Neal, Bruce; et al.
Abstract: Objectives: Population-level replacement of discretionary (i.e, table/cooking) salt with potassium-enriched salt substitutes is a promising strategy to reduce blood pressure (BP) and prevent cardiovascular disease (CVD). This may be particularly impactful in countries like China where sodium intake is high, mainly from discretionary salt use, and where potassium intake low. However, hyperkalemia resulting from potassium-enriched substitutes and its adverse CVD consequences are of concern for those with chronic kidney disease (CKD). We aimed to estimate the benefits and risks of nationwide replacement of discretionary salt with potassium-enriched salt substitute on CVD mortality in Chinese CKD patients. Methods: We used a comparative risk assessment framework and incorporated existing data and corresponding uncertainties from randomized trials, the China National Survey of CKD, the Global Burden of Disease study, and the CKD Prognosis Consortium. We estimated averted CVD mortality from reduced BP subsequent to salt substitution in CKD patients (defined as estimated glomerular filtration rate <60 mL/min per 1.73 m2) stratified by age and sex. Additional CVD deaths from hyperkalemia due to salt substitution were modelled in CKD patients stratified by kidney function. The robustness of the primary model was evaluated in a series of sensitivity analyses where key model assumptions and inputs were altered. Results: Nationwide implementation of potassium-enriched salt substitution would prevent an estimated 29, 735 (95% uncertainty interval: 13, 018–50, 403) CVD deaths/year among CKD patients by reducing BP, while the increased potassium intake could potentially produce an estimated 9791 (6078–15, 941) additional hyperkalemia-related deaths (Table ). The net effect would be 19, 558 (3430–37, 959) fewer CVD deaths/year, corresponding to 7.4% (1.4–13.4) of annual CVD deaths in Chinese CKD patients. Net benefits were consistent in sensitivity analyses (Table). Conclusions: Despite the risks of hyperkalemia, nationwide potassium-enriched salt substitution in China would result in significant net benefit among CKD patients. Funding Sources: This analysis was conducted in collaboration with Resolve to Save Lives, an initiative of Vital Strategies. Resolve to Save Lives is funded by Bloomberg Philanthropies, the Bill & Melinda Gates Foundation, and Gates Philanthropy Partners, which is funded with support from the Chan Zuckerberg Foundation. Funding for this work was also provided by the National Health and Medical Research Council and UNSW Sydney. Supporting Tables, Images and/or Graphs: